EKSPLORASI NILAI VERNAKULAR PADA BANGUNAN KOLONIAL (Studi Kasus : Gedung Arsip Nasional) - Prasetyo, Dimas Adhi; Zulkarnain (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2025)
Vernacular architecture represents an organic form of architecture that evolves through human adaptation to climate, environment, and local culture. In Indonesia, vernacular principles were often adopted in colonial buildings as a response to tropical climatic conditions. This study aims to identify and analyze vernacular architectural values applied in colonial architecture, using the National Archives Building in Jakarta as a case study. This research employs a qualitative descriptive method, with data collected through literature review, visual documentation, and secondary-based observation. The analysis refers to Paul Oliver’s (1997) theory of vernacular architecture, which outlines six principal characteristics.The findings reveal that the National Archives Building fulfills four of the six vernacular characteristics: climate responsiveness, use of local materials, natural and honest aesthetics, and efficiency and sustainability. However, local wisdom–based and participatory aspects were not identified due to the colonial construction process. This study demonstrates that colonial architecture in Indonesia reflects a hybrid adaptation rather than a purely European architectural expression.